Pengaruh Sistem Kontrak Bunga Cengkeh (Eugenia Aromaticum) terhadap Pendapatan Petani di Desa Pusakamulya Kecamatan Kiarapedes Kabupaten Purwakarta - Lily Sumarti; Iyep Mugni Muta’ali (Lembaga Penelitian dan Pengabdian Universitas Winaya Mukti, 2018)
The aim of this research is get the influence product clove farmer that contract system to income farmer’s. This research was conducted in Pusaka Mulya Village Kiara Pedes District Purwakarta Regency West Java Province. Theresearch time from May until August 2015. Input sampling with Stratification Random Sampling Methode. Analysis data with t test different two avarage to income. The result t test showed t test = 0,01 and t(α = 5%) = 2,024 result two system different, that income decrease that contract.